Fano resonances in near-field absorption in all-dielectric multilayer structures. (5th November 2018) - Kang, Byungjun; Fujii, Minoru; Nesterenko, Dmitry V; Sekkat, Zouheir; Hayashi, Shinji
Abstract: Extending our previous studies on metal-dielectric multilayer structures, we demonstrate the feasibility of generating and controlling high-Q Fano resonances in all-dielectric multilayer structures. The structures studied consist of two waveguide layers (Ge-doped SiO2 and Al2 O3 layers) separated by spacer layers (SiO2 layers) and arranged in the Kretschmann attenuated total reflection geometry. From analyses based on the electromagnetic theory, we reveal that the Fano resonance arises from the interaction between a broad waveguide mode supported by the Ge-doped SiO2 layer and a sharp waveguide mode supported by the Al2 O3 layer. This mechanism allows us to generate similar Fano resonances with both the p - and s -polarized incident light. Although the Fano resonances based on radiative modes in a variety of nanostructures and metamaterials have been reported to appear only in the far-field responses, we show that the present Fano resonances appear not only in the far-field reflection spectra but also in the near-field absorption spectra.